Student's guide to writing college papers - Turabian, Kate L (Chicago guides to writing, editing, and publishing, 2010)
Designed for less advanced writers than Turabian's Manual of Writers of Research Papers, Theses, and Dissertations, Seventh Edition, Gregory G. Colomb and Joseph M. Williams here introduce students to the art of defining a topic, doing high-quality research with limited resources, and writing an engaging and solid college paper. The Student's Guide is organized into three sections that lead students through the process of developing and revising a paper